The Effect of Green Logistics Practices, Digital Order Tracking Transparency, and Transportation on Last Mile Delivery Performance and Its Implications for Logistics Customer Satisfaction - Kurniawan, Angga Tri Hanggara; Maniah, Maniah; Purnomo, Agus (Dinasti Publisher, 2026)
This study examines the effects of Green Logistics Practices, Digital Order Tracking Transparency, and Transportation on Last Mile Delivery Performance and their implications for Logistics Customer Satisfaction among courier and logistics service customers at PT Pos Indonesia Situbondo Branch. A quantitative explanatory research design was employed. Data were collected through questionnaires distributed to 131 respondents selected using stratified random sampling from a population of 188 customers. The data were analyzed using Structural Equation Modeling Partial Least Square with Smart PLS3. The results demonstrate that Green Logistics Practices, Digital Order Tracking Transparency, and Transportation have positive and significant effects on Last Mile Delivery Performance. These variables also have positive and significant direct effects on Logistics Customer Satisfaction. Furthermore, Last Mile Delivery Performance has a positive and significant effect on Logistics Customer Satisfaction and acts as a mediating variable that strengthens the influence of Green Logistics Practices, Digital Order Tracking Transparency, and Transportation on customer satisfaction. These findings highlight the importance of sustainable logistics practices, transparent digital information systems, and reliable transportation in enhancing last mile delivery performance and customer satisfaction. The study provides practical insights for logistics service providers in improving service quality through integrated and sustainable logistics strategies.